Sentinel Bleeding as a Sign of Gastroaortic Fistula Formation after Oesophageal Surgery - M. Uittenbogaart; M. N. Sosef; J. van Bastelaar (Case Reports in Surgery)
Gastroaortic fistula formation is a very rare complication following oesophageal resection and, in most cases, leads to sudden death. We report the case of a 65-year-old male with an adenocarcinoma of the oesophagus who underwent neoadjuvant chemoradiation followed by a minimally invasive transthoracic oesophagectomy with gastric tube reconstruction and intrathoracic anastomosis. After an uneventful postoperative course and hospital discharge, the patient reported blood regurgitation on postoperative day 23. Endoscopy revealed an adherent blood clot on the oesophageal wall, which after dislocation caused exsanguination. Autopsy determined the cause of death being massive haemorrhage due to a gastroaortic fistula. The sudden onset of haemorrhage makes this condition particularly difficult to treat. Recognition of warning signs such as thoracic or epigastric pain, regurgitation of blood, or the passing of bloody stools or melena is crucial in the early detection of fistula and may improve patient outcome.